Studies on Biodiversity and Physico-chemical Properties of Carambola (Averrhoa Carambola L.) in Nagaland - Pongener, Meyijungla; Sarkar, Animesh; Humtsoe, Lisenbeni (International Journal of Bio-resource and Stress Management, 2022)
An experiment on the biodiversity and physicochemical properties of carambola (Averrhoa carambola was conducted in the Department of Horticulture, Nagaland University, SASRD, Medziphema Campus, Nagaland, India during February−April, 2021. 22 carambola genotypes were collected randomly from different locations (altitude 150−360 m MSL) of Dimapur district in Nagaland to identify the magnitude of variability and to study the plant morphological and biochemical properties of collected fruits. Ethnobotanical uses, medicinal and ayurvedic properties in different parts of carambola were documented by interrogation and questionaries from villagers during exploration. Majority of the genotypes were recorded to have spreading tree habit. The variation in fruit weight (84.66±38.72 g), fruit volume (66.32±33.33 cc), TSS (5.55±0.25° Brix), vitamin C content (26.57±6.77 mg 100 g-1), titratable acidity (0.29±0.13%), total sugar (8.32±1.44%), reducing sugar (7.62±1.33%) and oxalic acid (1.22±0.30%) was noted in different genotypes. The desirable characters with high heritability coupled with high genetic advance as percent of mean were recorded in fruit weight (98.20% and 92.52%), reducing sugar (97.40% and 36.05%), titratable acidity (99.90% and 92.97%) and oxalic acid (99.70% and 53.79%). Genotype-2 and Genotype-21 were considered as homogenous and more similar with less coefficient value (0.68) followed by Genotypes-13 and Genotypes-15 (2.10). Less acidity (0.19−0.20%), high Vitamin-C (37.87 mg 100 g-1 pulp) and high reducing sugar (9.28−9.45%) were noticed in Genotype-10 and Genotype-16 that stands as most promising genotypes in respect of biochemical composition of fruits.